RESPON AKTIVITAS AMILASE DAN PROTEASE IKAN GURAMI Osphronemus gouramy Lac. TERHADAP PERBEDAAN TEMPERATUR AIR - Dwiyan Oktavianto; Untung Susilo; Slamet Priyanto (Scripta Biologica, 2014)
Research to determine the activity of amylase and protease digestion gourami on various temperature has been carried out experimentally using a completely randomized design (CRD) with 3 treatments and 4 replications. The treatments were included gourami nurturing on water temperature 24oC (P1), gourami nurturing on water temperature 28oC (P2), and gourami nurturing on water temperature 32oC (P3). The results the amylase activity is showed no significant difference between treatments (P>0,05) where as protease activity showed there are significant differences between treatments (P0≤0,05). In conclusion, the difference in protease activity of gourami occured in water temperature 24oC (P1) and 28oC (P2) and the protease activity was highest at 28oC water temperature, but the amylase activity did not difference.